Case reportMadelung’s disease in a patient with chronic renal insufficiency: a case report and review of literature - Bergler-Czop, Beata; Wcisło-Dziadecka, Dominika; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Madelung’s disease (benign symmetric lipomatosis, Launois-Bensaude syndrome) was described for the first time in the middle of the 19 th century. This disorder concerns mainly men between 30 and 60 years of age. Patients often suffer from coexisting ailments, such as hepatic function disorders, polyneuropathy, diabetes, gynecomastia, hyperuricemia and deviations of lipid management parameters. Treatment of benign symmetric lipomatosis consists mainly in fat tissue sucking or injection lipolysis. Patients often have to wear special clothes correcting the deformed figure. We are presenting a case of a female patient with diagnosed Madelung’s disease, without alcohol abuse. Such abuse is reported in 90% of patients with this disease. Nevertheless, the patient has other typical (and described in the literature) hepatic and pancreatic function impairments, but also glomerular nephritis, which very rarely co-exists with benign symmetric lipomatosis.